Expandindo os limites da gramática: a multifuncionalidade linguístico-discursiva da construção NÃO pré-verbal em Redações de Vestibular - Assis, Dalva Lobão (2016)
Negation is a linguistic universal event present in all languages; each one of them reveals particular forms of manifesting the act of denying, naturally mental, human in excellence. This work aims at describing the discursive-linguistic functioning of one of the negation forms in Portuguese, the pre-verbal NO, particularly in Vestibular entrance Essays, based on the linguistic Functionalism to American side, especially in the sociocognitiva approach of the grammaticalization process (GIVÓN, 1979, 1984,1990, 2012; TRAUGOTT, 1984; HOPPER, 1987; TRAUGOTT e HEINE, 1991; HEINE et alii, 1991). We compared the traditional and functionalist approaches concerning the negation adverb NO, taking into account the possibility of the pre-verbal NO, more specifically, constituting a correlated negative construction. Then, we described the uses of the construction of the pre-verbal NO in the textual genre in focus, verifying the most and least prototypical of such uses, as well as recursive and encapsulated forms of such construction. We concluded, finally, that the discursive-linguistic functioning of the pre-verbal NO could present a synchronic path of grammaticalization in frank change, considering more connective and modalizadores-argumentative uses, given the constitution of a correlated negative construction, specifically in opinion essays, written by candidates of the 2013 Vestibular, from Universidade Estadual da Paraíba.